How AI Impacts Urban Living and Public Health 17th International Conference, ICOST 2019, New York City, NY, USA, October 14-16, 2019, Proceedings - Pagán, José; Mokhtari, Mounir; Aloulou, Hamdi; Abdulrazak, Bessam; Cabrera, María Fernanda (Information Systems and Applications, incl. Internet/Web, and HCI, 2019)
This open access book constitutes the refereed proceedings of the 17th International Conference on String Processing and Information Retrieval, ICOST 2019, held in New York City, NY, USA, in October 2019. The 15 full papers and 5 short papers presented in this volume were carefully reviewed and selected from 24 submissions. They cover topics such as: e-health technology design; well-being technology; biomedical and health informatics; and smart environment technology. .